An Expanded Neuroimmunomodulation Axis: sCD83-Indoleamine 2,3-Dioxygenase—Kynurenine Pathway and Updates of Kynurenine Pathway in Neurologic Diseases - Bo, Li; Guojun, Tan; Li, Guo (Frontiers in Immunology, 2018)
Many neurologic diseases are related to autoimmune dysfunction and a variety of molecules or reaction pathways are involved in the regulation of immune function of the nervous system. Soluble CD83 (sCD83) is the soluble form of CD83, a specific marker of mature dendritic cell, which has recently been shown to have an immunomodulatory effect. Indoleamine 2, 3-dioxygenase (IDO; corresponding enzyme intrahepatic, tryptophan 2,3-dioxygenase, TDO), a rate-limiting enzyme of extrahepatic tryptophan kynurenine pathway (KP), participates in the immunoregulation through a variety of mechanisms solely or with the synergy of sCD83, and the imbalances of metabolites of KP were associated with immune dysfunction. With the complement of sCD83 to IDO-KP a previously known immunomodulatory axis, this review focused on an expanded neuroimmunomodulation axis: sCD83-IDO-KP and its involvement in nervous system diseases.